Error Analysis of Class XI Students of SMA in Solving Matrix Problems in terms of Mathematical Ability - Hasbi, Muh; Lapalesa, Ester; Anggraini, Anggraini; Nasir, Rahma (Universitas Islam Ahmad Dahlan (UIAD), 2023)
This research aims to describe the types of errors made by students in solving matrix problems. The subjects in this research were three students of class XI MIPA SMA 5 Palu who were divided into three categories based on their level of mathematical ability, namely students with high, medium, and low mathematics ability. The selection of these three students was based on students report cards which were categorized into three types, namely high, medium and low, which were then selected through considerations, namely students who were able to take part in the entire of data collection activities carried out by researchers as well as considerations from mathematics subject at the school. This type of research is descriptive research with a qualitative approach. Data collection was carried out by administering written tests and interviews. The results of this research show that students of class XI MIPA SMA Negeri 5 Palu made mistakes in solving questions (1) high mathematics ability students made conceptual mistakes, namely students were wrong in writing the concept of matrix multiplication that had different orders. (2) students with moderate mathematics ability made procedural errors, namely students were wrong in carrying out the steps of solving the problem and students in solving the problem did not reach that students do not write the sign of mathematical operations that should be used. (3) students with low mathematics ability made conceptual errors, namely students did not solve the problems given, only rewrote the matrix members. Procedural errors, namely students are not careful in understanding the question instruction so that the steps for solving the problem are not appropriate and students do not solve the problem until the final stage. Technical errors, namely students are wrong in doing calculations so that the students answers do not match the alternative answers. This research is highly recommended for other researchers to explore further because the coverage of the matrix material is quite broad so researchers cannot discuss everything in this research and there are many more reviews that need to be analyzed through this material.